Board structure and firm value: A study on listed banking firms in the Asian emerging markets - Zulkafli, Abdul Hadi; Amran, Azlan; Samad, M. Fazilah Abdul (Inderscience, 2010)
The banking sector in developing countries is regarded as an engine of economic growth (Arun, 2004). It is believed that corporate governance is necessary to ensure a sound financial system and, consequently, help develop the country's economy. Using a Pooled Generalised Least Squares (GLS) regression model, the relationship between board structure and bank's performance is analysed. A total of 107 listed banks in nine countries of the Asian emerging markets were included in the study. It is evidenced that only one aspect of board structure, which is CEO Duality, is positively significant, with market-based corporate performance.